2014
DOI: 10.4000/jsa.14072
|View full text |Cite
|
Sign up to set email alerts
|

El estilo Río Bec visto desde Dzibanché y Kohunlich

Abstract: Hallazgos recientes (2009) en Dzibanché arrojan nueva luz sobre la relación de este sitio con su vecino más cercano, Kohunlich, y la región Río Bec. Nuevas hipótesis permiten explicar la penetración del estilo arquitectónico Río Bec en un sitio tan distante como Kohunlich, especialmente si se considera la cercanía con Dzibanché, un sitio qué, por su tamaño, fué el sitio de gran dominio. Así mismo se proponen nuevas ideas sobre la dinastía Kan durante el Clásico tardío [Palabras claves: Dzibanché, Kohunlich, Rí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Later, around AD 600-700, a fourth building was built at the center. The absence of benches (banquetas) and domestic use artifacts seems to confirm that this complex had an administrative function [34,38,40]. The complex has many remains of plasters in internal walls (with a subtle pink color), doorposts, and, in the exterior, faҫades.…”
Section: The Archaeological Sitementioning
confidence: 83%
See 2 more Smart Citations
“…Later, around AD 600-700, a fourth building was built at the center. The absence of benches (banquetas) and domestic use artifacts seems to confirm that this complex had an administrative function [34,38,40]. The complex has many remains of plasters in internal walls (with a subtle pink color), doorposts, and, in the exterior, faҫades.…”
Section: The Archaeological Sitementioning
confidence: 83%
“…In the Late Classic there was a short period of political instability with clear signs of violence, followed by a peaceful split of the Kaan dynasty (7th century): a member of the family stayed in Dzibanché and the k'uhul ahau settled in Calakmul. Dzibanché maintained a prominent political position in the area until the 8th century, then the importance of the site was reduced: it was first transformed into a small settlement and then abandoned in the Late Pos tclassic [33][34][35][36][37][38][39]. The three Grupo Principal buildings studied for this project are: Pequeña Acrópolis, Plaza Pom, and Structure 2 "Templo de los Cormoranes" (Figure 1).…”
Section: The Archaeological Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Broadly speaking, if the burst of non-royal, monumental-residence constructions over the Lowlands was initiated by AD 700-750, it may be correlated in time with the later weakening of k'uhul ajaw authority. As a case in point, research across many Río Bec residential groups of monumental residences has shown that local societies were irmly structured and prosperous throughout the Late-Terminal Classic, although with extremely weak kingship institutions (Arnauld et al 2014b; Fowler and Arnauld 2013; Arnauld and Nondédéo 2010; Nondédéo et al Nalda and Balanzario 2014). Effective political authority should be distinguished from apex positions in local or regional hierarchies.…”
Section: Formation Of Large Intermediate Social Groups and The End Ofmentioning
confidence: 99%
“…The Terminal Classic period saw a regional diffusion process of the Río Bec architectural style over the central lowlands, from Kohunlich in the east to El Tigre in the west, from Becan in the north to Naachtun in the south (Benavides Castillo 2007; Nalda and Balanzario 2007; Nondédéo 2003; Nondédéo et al 2011; Vargas Pacheco 2007). This late diffusion process should not be interpreted as reflecting a generalized dominance of Río Bec elites, but rather as the result of exogamic alliances among high-ranking houses in distant centers (Arnauld and Nondédéo 2010).…”
Section: Rio Bec Architecture and Social Reconstructionmentioning
confidence: 99%